The Interpretation of International Investment Treaties: The Application of MFN Clauses to Matters of Dispute Settlement in BITs - Aabed, Amr Mostafa, Abdo (AUC Knowledge Fountain, 2021)
The decisions of the arbitral tribunals have been under heavy attack for the inconsistent and unintended interpretations that went beyond the intent of the parties as it is expressed in the treaty provisions. One of these misinterpreted provisions is the MFN clause. Many tribunals have used this clause to allocate the adjudicatory authority between international arbitration and domestic courts. The problem of this application is a matter of treaty interpretation that is governed by the international rules of interpretation in the VCLT. These rules provide a balance approach to treaty interpretation and recognize equally the legitimate rights and interests of the host states and foreign investors. The root cause of the interpretive problems in investor-state arbitration is the neglect and misapplication of the international rules on treaty interpretation. Although, interpretation is not an exact science, it is still a science requiring the application of particular rules to produce correct results. These rules are established to respect the states' intentions, not to deny any relevance of these intentions to interpretation. A full compliance with these rules will lead to correct interpretations and ensure that these interpretations are consistent with parties’ intentions as it is expressed in the terms of the treaty. The duty of adjudicators is to discover the meaning of the treaty provisions; examining evidence according to the logical sequence of the rules of interpretation in the VCLT, and provide the parties with impartial interpretations. It is not their duty to harmonize dispute settlement arrangements in BITs or impose this harmonized system upon states against their intent. The actual application of these rules of interpretation works as a roadmap to reach the consistent meanings of the treaty provisions and will give us a negative answer to the question of whether the MFN clause should be applied to dispute settlement provisions in BITs or not.